Hubungan antara Stres Akademik dan Dukungan Sosial Orang Tua dengan Prestasi Akademik Mahasiswa Fakultas Kedokteran Universitas Tanjungpura Angkatan 2020: Hasil Penelitian - Teofilus Sintan; Ita Armyanti; Agustina Arundina Triharja Tejoyuwono (PT Kalbe Farma Tbk., 2025)
Introduction: First-year medical faculty students are one of the populations that often experience academic stress. Academic stress can affect academic achievement. Parents’ social support will make their children able to undergo lectures and show good academic achievement. This research aims to determine the relationship between academic stress and parents’ social support on academic achievement among Medicine Faculty students, Tanjungpura University batch 2020. Methods: A cross-sectional observational analytical study. There search population was Medicine Faculty students, Tanjungpura University batch 2020. The research sample was 239 people, chosen by simple random sampling technique. Data was obtained from filling in personal data, student academic stress scale (SASS) questionnaire, parents’ social support questionnaire, and cumulative grade point average. Bivariate analysis used the Spearman correlation test. Results: The result of the correlation test for academic stress and academic achievement was p=0,146; r=0,094; and the correlation test for parents’ social support and academic achievement was p=0,016; r=0,156. Conclusion: There is an insignificant positive relationship between academic stress and academic achievement and a significant positive relationship between parents’ social support and academic achievement.